Detection of Bartonella schoenbuchensis (sub)species DNA in different louse fly species in Saxony, Germany: The proof of multiple PCR analysis necessity in case of ruminant-associated bartonellae determination - Vogt, Isabelle; Schröter, Stephanie; Schreiter, Ruben; Sprong, Hein; Volfová, Karolina; Jentzsch, Matthias; Freick, Markus (Veterinary medicine and science, 2024)
BACKGROUND: Hippoboscid flies are bloodsucking arthropods that can transmit pathogenic microorganisms and are therefore potential vectors for pathogens such as Bartonella spp. These Gram-negative bacteria can cause mild-to-severe clinical signs in humans and animals; therefore, monitoring Bartonella spp. prevalence in louse fly populations appears to be a useful prerequisite for zoonotic risk assessment. METHODS: Using convenience sampling, we collected 103 adult louse flies from four ked species (Lipoptena cervi, n = 22; Lipoptena fortisetosa, n = 61; Melophagus ovinus, n = 12; Hippobosca equina, n = 8) and the pupae of M. ovinus (n = 10) in the federal state of Saxony, Germany. All the samples were screened by polymerase chain reaction (PCR) for Bartonella spp. DNA, targeting the citrate synthase gene (gltA). Subsequently, PCRs targeting five more genes (16S, ftsZ, nuoG, ribC and rpoB) were performed for representatives of revealed gltA genotypes, and all the PCR products were sequenced to identify the Bartonella (sub)species accurately. RESULTS AND CONCLUSIONS: The overall detection rates for Bartonella spp. were 100.0%, 59.1%, 24.6% and 75.0% in M. ovinus, L. cervi, L. fortisetosa and H. equina, respectively. All the identified bartonellae belong to the Bartonella schoenbuchensis complex. Our data support the proposed reclassification of the (sub)species status of this group, and thus we conclude that several genotypes of B. schoenbuchensis were detected, including Bartonella schoenbuchensis subsp. melophagi and Bartonella schoenbuchensis subsp. schoenbuchensis, both of which have previously validated zoonotic potential. The extensive PCR analysis revealed the necessity of multiple PCR approach for proper identification of the ruminant-associated bartonellae.
Keywords: Lipoptena cervi; DNA bakterií; Humans; Phthiraptera; Hippobosca equina; lidé; zvířata; Germany; Bartonella schoenbuchensis; Německo; přežvýkavci; DNA; DNA, Bacterial; Bartonella schoenbuchensis subsp. melophagi; Hippoboscidae; Bartonella; Melophagus ovinus; Diptera; Lipoptena fortisetosa; polymerázová řetězová reakce; Polymerase Chain Reaction; Animals; multiple polymerase chain reaction analysis; Ruminants